Application of positron emission tomography in physical medicine - Masud, M; Fujimoto, T; Watanuki, S; Miyake, M; Itoh, M; Tashiro, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):110-115. The abstract of this article is available on the PubMed website